2008
DOI: 10.1016/j.ejor.2006.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A multicriteria facility location model for municipal solid waste management in North Greece

Abstract: Cataloged from PDF version of article.Up to 2002, Hellenic Solid Waste Management (SWM) policy specified that each of the country’s 54 prefectural governments\ud plan its own SWM system. After 2002, this authority was shifted to the country’s 13 regions entirely. In this\ud paper, we compare and contrast regional and prefectural SWM planning in Central Macedonia. To design the prefectural\ud plan, we assume that each prefecture must be self-sufficient, and we locate waste facilities in each prefecture. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(79 citation statements)
references
References 18 publications
1
72
0
6
Order By: Relevance
“…Neto et al [22] investigate the environmental impact factors along the supply chain and propose a multi objective programming based framework in modeling and optimizing the design of logistic networks. Erkut et al [23] present a multi-criteria mixed-integer linear programming formulation to solve a locationallocation problem regarding municipal waste management.…”
Section: Related Literaturementioning
confidence: 99%
“…Neto et al [22] investigate the environmental impact factors along the supply chain and propose a multi objective programming based framework in modeling and optimizing the design of logistic networks. Erkut et al [23] present a multi-criteria mixed-integer linear programming formulation to solve a locationallocation problem regarding municipal waste management.…”
Section: Related Literaturementioning
confidence: 99%
“…Multiplying all maximization objective functions by −1, we obtain the multi-objective minimization model [24]. …”
Section: Methodsmentioning
confidence: 99%
“…For most case studies, the generic model is simplified in order to adapt the characteristics of the problems with less objectives and/or smaller network. Only two exceptions are given by Coruso et al (1993) and Erkut et al (2008), in which additional objectives have to be introduced in order to improve the utilization of resource. Besides, it is also observed that the introduction of adjustment parameters , and improves the flexibility and adaptability of the environmental impact objective function, as compared with Coruso et al (1993), Eiselt and Marianov (2014) and He et al (2006).…”
Section: Comparison Of the Case Studies In Previous Research Workmentioning
confidence: 99%